A Pt/ITO/CeO2/Pt memristor with an analog, linear, symmetric, and long-term stable synaptic weight modulation - Hyung Jun Kim; Minju Kim; Keonwon Beom; Hyerin Lee; Chi Jung Kang; Tae-Sik Yoon (APL Materials, 2019)
Analog synaptic weight modulation that is linear, symmetric, and exhibits long-term stability is demonstrated by the resistance changes in a Pt/indium-tin-oxide (ITO)/CeO2/Pt memristor. Distinct from a Pt/CeO2/Pt memristor without the ITO layer, which shows highly nonlinear and asymmetric resistance changes, the Pt/ITO/CeO2/Pt memristor exhibits linear and symmetric resistance changes in proportion to the number of voltage applications with opposite polarities for potentiation and depression behaviors. The Pt/CeO2/Pt memristor also displays high long-term stability of modulated synaptic weight over time, which originates from the ITO layer acting as a reservoir of oxygen ions drifted from the CeO2 layer to retain the resistance change. Comparison of the results for the Pt/CeO2/Pt and Pt/ITO/CeO2/Pt memristors confirms the role of ITO in the linearity, symmetry, and long-term stability of the resistance change in CeO2-based memristors for use as artificial synapses in neuromorphic systems.